Trimethoprim-Sulfamethoxazole-Induced Aseptic Meningitis: A New Approach - Elmedani, Sarah (Cureus, 2021)
Inflammation of the meningeal linings of the central nervous system (CNS), also known as meningitis, is one of the serious presentations in the emergency because it carries high morbidity and mortality. The most common cause is pus-producing organisms. However, non-suppurative meningitis, termed aseptic meningitis, is another cause of meningeal inflammation. Many etiologies stand behind aseptic meningitis. Those etiologies include viral and non-viral, drug-induced, malignancy, and systemic inflammation. Drug-induced aseptic meningitis is a rare type of meningitis. Although it is easily treated, it can be a challenging disease if not present in the differential diagnosis. It is commonly associated with nonsteroidal anti-inflammatory drugs (NSAIDs). Nonetheless, other medications have been also reported to cause aseptic meningitis, including antibiotics. Trimethoprim-sulfamethoxazole (TMP-SMX) is one of the most prescribed antibiotics as a prophylactic and therapeutic drug due to its effectiveness and low cost. Although immunocompromised patients are at a higher risk to develop aseptic meningitis, immunocompetent patients are also at risk. Unrelated to the source of the infection, TMP-SMX carries a risk of aseptic meningitis and should be considered as an etiology in patients presenting with meningeal signs and symptoms. Hereby, we report a young immunocompetent patient who developed aseptic meningitis eight days after being prescribed TMP-SMX. Like all drug-induced aseptic meningitis, all his symptoms resolved two days after stopping the medication.